From waste to resource: demystifying the policy challenges and identifying opportunities for a circular economy in Zambia - Clube, Rebecca K. M.; Hazemba, Malonga (Frontiers in Sustainability, 2024)
Policy plays a significant role in accelerating or hindering a circular shift; Governments can set longterm visions and drive legislative change to create an enabling environment. Reflecting the regional picture, Zambia is experiencing increasing waste burdens paralleling a growing population and economic development. The current linear management approach is characterised by low collection rates, inadequate disposal, and limited waste revalorisation. From a sustainable development perspective, how waste is managed impacts pressing issues such as climate change and public health. The concept of the Circular Economy (CE) has gained global and regional interest given its potential to transform how resources are viewed and managed. Circular strategies may help reduce waste burdens and create local socioeconomic opportunities whilst safeguarding the environment. This qualitative study uses document review and expert interviews to explore the current waste management regime in Zambia and understand if and how circularity is being embedded into the policy approach. The findings suggest that the CE is potentially highly relevant for Zambia, but there are various policy challenges that could impede its successful integration into the national agenda. These challenges relate to governance and coordination; gaps in implementation and enforcement; a restrictive licensing approach; obstacles to innovation and new entrants; as well as the role of informal sector actors. The challenges also point to opportunities to overturn these policy shortfalls, which also presents future research avenues. literature. Then, section 5 discusses some policy opportunities to overturn the challenges identified, before concluding the research in section 6.This section introduces relevant literature surrounding the CE concept, its relevance for Africa, and in particularly for Zambia. Then, the importance of policy for a CE is introduced, with reference to the existing research encompassing Sub-Saharan Africa,